The dialectics of discipleship: Karl Barth, sanctification and theological ethics - Swann, Chris (T&T Clark enquiries in theological ethics, 2023)
"Critically evaluates the under-appreciated emphasis on discipleship in Barth's late doctrine of sanctification (in Church Dogmatics IV/2) and establishes its significance for theological ethics"--